2012
DOI: 10.3109/0142159x.2012.714884
|View full text |Cite
|
Sign up to set email alerts
|

Optimal learning in a virtual patient simulation of cranial nerve palsies: The interaction between social learning context and student aptitude

Abstract: Background Simulation in medical education provides students with opportunities to practice interviews, examinations, and diagnosis formulation related to complex conditions without risks to patients. Aim To examine differences between individual and team participation on learning outcomes and student perspectives through use of virtual patients (VPs) for teaching cranial nerve (CN) evaluation. Methods Fifty-seven medical students were randomly assigned to complete simulation exercises either as individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 11 publications
0
20
0
2
Order By: Relevance
“…Traditionally, CNs have been taught using two‐dimensional (2D) images in a didactic lecture, in combination with plastic models or cadaver material in a hands‐on laboratory class. As CN content is difficult, academics have used a range of strategies to engage students, including 3D virtual simulations (Yeung et al, ; Nowinski et al, , Johnson et al, ), gaming avatars (Richardson‐Hatcher et al, ), videos (Azer et al, ), models (Zhang and He, ), games (Jones et al, ), songs (Bromfield, ; Williams, ), and drawings (Bolek, ). However, evidence of these strategies' effectiveness in improving CN knowledge is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, CNs have been taught using two‐dimensional (2D) images in a didactic lecture, in combination with plastic models or cadaver material in a hands‐on laboratory class. As CN content is difficult, academics have used a range of strategies to engage students, including 3D virtual simulations (Yeung et al, ; Nowinski et al, , Johnson et al, ), gaming avatars (Richardson‐Hatcher et al, ), videos (Azer et al, ), models (Zhang and He, ), games (Jones et al, ), songs (Bromfield, ; Williams, ), and drawings (Bolek, ). However, evidence of these strategies' effectiveness in improving CN knowledge is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a significant ATI effect identified that students in the team treatment attained a mean post-test score approximately 24% higher than students in the individual treatment at specific aptitudes. Johnson et al (2013) observed this same ATI effect with 57 second-year medical students; at pre-test scores ≤50%, students in the team treatment scored significantly higher (21%) on the knowledge post-test as compared to students in the individual treatment.…”
Section: Discussionmentioning
confidence: 52%
“…This control allows users to explore a variety of patient scenarios and to observe a wide range of abnormal physical findings in a self-directed manner. While our findings from this study and results from Johnson et al (2013) suggest that NERVE exercises may best be implemented in small collaborative team contexts, we recognize that the strain on medical education resources may challenge educators to successfully plan for such activities. Limited small-group learning spaces in institutional facilities and restrictions on contact hours allowed in the curriculum may necessitate a selection of self-directed, individualized learning opportunities.…”
Section: Directions For Future Researchmentioning
confidence: 68%
See 1 more Smart Citation
“…Kleinsmith et al (2015), Rivera-Gutierrez et al (2014), Lyons, Johnson, Khalil, and Cendan (2014), and Johnson et al (2014Johnson et al ( , 2013 report findings from controlled experiments completed during the first four years of R&D that compared various aspects of VP simulations to inform the design of the system and advanced VP simulation research, such as individual versus small group use of the system, use of the system under competitive versus non-competitive conditions, the use of reflective questions embedded during versus after the simulation, instructor-led content delivery versus independent self-study of the content prior to use, and the use of an open-chat versus closed menu user interface.…”
mentioning
confidence: 99%